(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The antidiarrhoeal activity of aqueous leaf extract of Momordica charantia was evaluated on castor oil induced diarrhea, gastrointestinal transit, intestinal fluid accumulation and gastric emptying in mice. An inhibitory function against beaver oil has been seen in the aqueous extract from its leaves. The gastrointestinal community and fluid release by the extract mean that an anti-diarrhoeal mechanical operation is undertaken by the current extract.